Konflik Internal antara Bupati dan Wakil Bupati Aceh Besar Tahun 2019 - Muhajir, Rahmad; Agustino, Leo; Muradi, Muradi (Mahesa Research Center, 2021)
The 2017 Aceh Besar Pilkada began with the people's desire for a new, better government in Aceh Besar, and in the end the candidate pairs of regents and vice regents namely Mawardi Ali and Tgk Husaini A Wahab won by winning 110,074 votes or winning with 57, 10 %. This victory was obtained from 18 sub-districts out of a total of 23 sub-districts, but after a year of serving as the Regent and his deputy, an internal conflict arose between the two. This research was conducted to dig deeper into the causes of the conflict, so that if possible, a resolution of this conflict could be obtained. The research method used is qualitative in which data is obtained through direct interviews with the two regional leaders (regent and deputy regent) and people who are in the vortex of the conflict. The results of this study indicate the conflict is due to differences in views between the two where the regent feels that his authority and work assignments are in accordance with their respective administrative positions. However, according to the deputy regent there is an agreement between the two that has not been fulfilled, resulting in conflict between the regent and deputy regent, but this conflict can be resolved properly through discussions or deliberations facilitated by a third party.